Analysing mistranslation in public signs within linguistic landscapes - Ahmed, Khawlah (International journal of linguistics, literature and culture, 2025)
This study explores the phenomenon of mistranslations in public signage within multilingual environments, drawing on linguistic landscape theory, semiotics, and translation studies. By examining five case studies from diverse regions, the research identifies common sources of mistranslations, including linguistic factors, translation strategies, and socio-cultural influences. The analysis reveals that mistranslations often stem from literal translations that overlook idiomatic expressions and cultural nuances, leading to confusion and potential reinforcement of cultural stereotypes. The study underscores the need for improved translation practices and quality control measures to enhance the accuracy and cultural appropriateness of public signage. The findings contribute to the broader understanding of translation challenges in multilingual contexts and highlight the importance of considering both linguistic and cultural elements in translation practices.